PENDAMPINGAN DAN PELATIHAN PENINGKATAN KONDISI FISIK PADA UNIT KEGIATAN MAHASISWA BOLAVOLI UNIVERSITAS MUHAMMADIYAH SURAKARTA - Gatot Jariono; Nurhidayat Nurhidayat; Eko Sudarmanto; Sae Dikdaya Nyatara; Tunjung Marganingrum (Indonesian Collaboration Journal of Community Services, 2021)
The element of good physical condition is one of the supporting achievements of a sport but not only those basic technical skills become a supporting role for the achievement of an athlete's achievement. Mastery of basic techniques in a good volleyball game and good physical condition for athletes must certainly be considered by a coach to deliver athletes to the highest achievements. In principle, to achieve the goal of optimal achievement in each sport, it must be based on the principles of a sports science approach. The principles of modern training of each sport require specificity. Four elements that need to be possessed by individuals to achieve an optimal performance are (1) Physical development; 2) Technical Development; (3) Mental development, and 4) Champion Maturity. The objectives of community service are: (1) Providing knowledge to management and volleyball players about the physical components of volleyball players; (2) Providing knowledge of administrators, coaches, and athletes in the use of science and technology to make it easier to know what physical components I am good for volleyball players; and (3) Provide physical exercise manuals for administrators, coaches, and athletes to be more qualified and productive, where so far the administrators, coaches, and athletes only conduct training according to experience and do not document the progress of the athletes they train. The method implemented in this activity is based on the results of discussions between the proposer and partners. Furthermore, the researcher concludes that the priority of the problems agreed to be resolved during the community service implementation is to provide training on the physical condition of the Volleyball Student Activity Unit, Muhammadiyah University of Surakarta. Collecting data using the method of observation, interviews, and measurement of physical conditions. The results of this service can be concluded that mentoring and training to improve physical condition can help administrators and students who join UKM Bolavoli to be implemented in physical condition improvement exercises consisting of speed, agility, strength, explosive power, and endurance